A kind of hydrodemetallization catalyst and preparation method thereof

A catalyst with optimized alumina, carbon, and metal composition, prepared via dual aging and controlled impregnation, addresses the activity and stability issues of existing catalysts, enhancing hydrodemetallization performance for heavy oils.

CN117000255BActive Publication Date: 2025-01-03CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210456984.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-27
Publication Date
2025-01-03
Estimated Expiration
2042-04-27

AI Technical Summary

Technical Problem

Existing hydrodemetallization catalysts for heavy oil, particularly residual oil, suffer from inadequate activity and stability, necessitating improved preparation methods to enhance their performance.

Method used

A hydrodemetallization catalyst comprising alumina, carbon, and specific ratios of molybdenum and Group VIII metals, with a tailored pore structure and metal distribution achieved through a multi-step preparation process involving dual aging, ammonium bicarbonate treatment, and controlled impregnation with water-soluble polymers, to optimize catalyst performance.

Benefits of technology

The method significantly enhances the activity and stability of the catalyst, providing a suitable pore structure for macromolecular diffusion and metal deposition, resulting in improved hydrodemetallization efficiency for heavy oils.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117000255B_ABST
    Figure CN117000255B_ABST
Patent Text Reader

Abstract

The present invention discloses a hydrodemetallization catalyst and a preparation method thereof. The catalyst comprises a carrier component and a second active component, the second active component comprises molybdenum and a Group VIII metal, the carrier component comprises aluminum oxide, carbon and a first active component, the first active component comprises molybdenum and a Group VIII metal; the mass ratio of aluminum oxide to carbon in the carrier is 5.5 to 24.5; wherein, in terms of Mo atoms, the ratio of tetrahedral molybdenum to octahedral molybdenum in the catalyst is 0.13 to 0.25. The catalyst is applied to a residual oil hydrodemetallization catalyst, and both the activity and stability are significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a hydrodemetallization catalyst, in particular to a hydrodemetallization catalyst suitable for heavy oil, especially residual oil hydrotreating process and a preparation method thereof. Background Art

[0002] In recent years, the trend of heavy and inferior crude oil has become increasingly serious, but the market demand for light oil products has continued to increase. This has caused the hydrogenation technology, which is an important treatment route for heavy oil, to face new challenges. As the core of hydrogenation technology, the preparation technology and performance of catalysts are of great significance for the deep hydrogenation of heavy oil. As for the hydrogenation of residual oil, the residual oil hydrodemetallization reaction is one of the important chemical reactions occurring during the residual oil hydroprocessing process. Under the action of the catalyst, various metal compounds react with H2S to generate metal sulfides, which are then deposited on the catalyst and removed. The existence state of active metals on the catalyst carrier is bound to play an important role in the activity and stability of the catalyst.

[0003] CN102441399A discloses a method for preparing a hydrodemetallization catalyst, wherein a metal compound of group VIB and / or a metal compound of group VIII is prepared into an ammonia solution or an aqueous solution, and then impregnated with an alumina carrier, and the final catalyst is obtained by drying and roasting. CN1289640A discloses a method for preparing a supported hydrodemetallization catalyst, wherein the method uses a macroporous alumina carrier, and an ammonia solution or an aqueous solution of an active metal is sprayed onto the carrier in a spraying drum, and the method omits the normal temperature drying process of the carrier after impregnation, and the sprayed carrier is directly placed in a roasting furnace at a temperature of 300 to 450°C for roasting, and then gradually heated to 460 to 550°C, and kept at a constant temperature for 1 to 5 hours under air conditions. CN103785400A discloses a method for preparing a high-activity residue oil hydrodemetallization catalyst, which comprises the following steps: impregnating an alumina carrier with a polyol and / or a monosaccharide aqueous solution, performing a hydrothermal carbonization treatment in a sealed container after the impregnation, and then loading active metal components Mo and Ni on the carrier; finally, calcining the alumina loaded with the active components in a nitrogen atmosphere and then in an air atmosphere to obtain a residue oil hydrodemetallization catalyst.

[0004] The activity and stability of the hydrodemetallization catalyst prepared by the above method still need to be further improved. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention provides a hydrodemetallization catalyst and a preparation method thereof. When the catalyst is used in the hydrodemetallization reaction of residual oil, the activity and stability of the hydrogenation reaction can be significantly improved.

[0006] The first aspect of the present invention provides a hydrodemetallization catalyst, comprising a carrier component and a second active component, wherein the second active component comprises molybdenum and a Group VIII metal, the carrier component comprises alumina, carbon and a first active component, wherein the first active component comprises molybdenum and a Group VIII metal; the mass ratio of alumina to carbon in the carrier is 5.5 to 24.5, preferably 8.0 to 13.5; wherein in the catalyst, the ratio of the content of tetrahedral molybdenum to that of octahedral molybdenum, calculated as Mo atoms, is 0.13 to 0.25.

[0007] In the present invention, the Group VIII metal in the first active component is preferably nickel.

[0008] In the present invention, the second active component includes molybdenum and a Group VIII metal, and the Group VIII metal is preferably nickel.

[0009] In the present invention, based on the mass of the catalyst, the content of MoO3 is 5.0% to 20.0%, and the content of the Group VIII metal oxide is 2.0% to 6.0%.

[0010] In the present invention, based on the total MoO3 mass in the catalyst, the content of MoO3 in the first active component is 35.0% to 65.0%, and the content of MoO3 in the second active component is 35.0% to 65.0%.

[0011] In the present invention, based on the total mass of Group VIII metal oxides in the catalyst, the content of Group VIII metal oxides in the first active component is 35.0% to 65.0%, and the content of Group VIII metal oxides in the second active component is 35.0% to 65.0%.

[0012] In the present invention, the specific surface area of ​​the catalyst is 140 to 210 m 2 / g, the pore volume is 0.50~1.10mL / g, and the pore diameter is 13~25nm.

[0013] In the present invention, preferably, the specific surface area of ​​the catalyst is 165 to 200 m 2 / g, the pore volume is 0.85~0.95mL / g, and the pore diameter is 17~24nm.

[0014] In the present invention, the catalyst further comprises an auxiliary component, which is selected from at least one of fluorine, phosphorus, silicon or boron, preferably phosphorus. Based on the mass of the catalyst, the content of the auxiliary component in terms of oxide is 1.0% to 4.0%.

[0015] The second aspect of the present invention provides a method for preparing the above-mentioned hydrodemetallization catalyst, comprising the following steps:

[0016] (1) neutralizing an acidic aluminum salt solution with an alkaline aluminum salt solution, and subjecting the solution to primary aging to obtain a slurry;

[0017] (2) the slurry obtained in step (1) is evenly divided into slurry I and slurry II, a water-soluble polymer J1 is added to slurry II, and slurry I and slurry II are subjected to secondary aging and drying to obtain dried products I and dried products II;

[0018] (3) immersing the dried material I obtained in step (2) in an aqueous solution of ammonium bicarbonate, sealing and heat treating, and drying to obtain material A;

[0019] (4) immersing the dried material II obtained in step (2) in an aqueous solution of ammonium bicarbonate, sealing and heat treating, drying, impregnating the material with a first active component metal impregnation solution in an unsaturated impregnation manner, and drying to obtain material B;

[0020] (5) kneading material A and material B, forming, drying, and first calcining to obtain a carrier;

[0021] (6) The support obtained in step (5) is impregnated with the second active component metal impregnation solution in a saturated impregnation manner, dried, and subjected to a second calcination to obtain the catalyst.

[0022] In step (1) of the present invention, the acidic aluminum salt solution and the alkaline aluminum salt solution are added to the reaction kettle in a parallel flow.

[0023] In step (1) of the present invention, the acidic aluminum salt solution is one or more of aluminum sulfate solution, aluminum nitrate solution or aluminum chloride solution; the concentration of the acidic aluminum salt solution is 8g / 100mL to 28g / 100mL in terms of Al2O3. The alkaline aluminum salt solution is one or more of sodium metaaluminate solution and potassium metaaluminate solution; the concentration of the alkaline aluminum salt solution is 10g / 100mL to 50g / 100mL in terms of Al2O3.

[0024] In step (1) of the present invention, the neutralization reaction temperature is 75 to 120° C., the time is 30 to 150 minutes, and the pH value of the slurry is controlled to be 6.0 to 9.8 during the neutralization reaction. The pH value of the slurry is adjusted by controlling the addition rate of the acidic aluminum salt solution and the alkaline aluminum salt solution or by additionally adding an acid-base regulator during the neutralization reaction.

[0025] In step (1) of the present invention, the temperature of the primary aging is 90 to 240° C., the time is 50 to 240 minutes, and the pH value is 9.0 to 10.0.

[0026] In step (2) of the present invention, after the primary aging is completed, preferably, the slurry is first concentrated and then subjected to secondary aging, wherein the volume of the concentrated slurry is 30% to 70% of the original volume.

[0027] In step (2) of the present invention, no substance is added to the slurry I. The water-soluble polymer J1 added to the slurry II is one or more of polyethylene glycol, polyvinyl alcohol, polyacrylamide and methyl cellulose, preferably polyethylene glycol; the viscosity (20°C) of the water-soluble polymer J1 is 10 to 1000 mPa·s, and the viscosity (20°C) of the slurry II after adding the water-soluble polymer J1 is 120 to 660 mPa·s.

[0028] In step (2) of the present invention, the secondary aging temperature is 120-270° C., the time is 40-190 minutes, and the secondary aging temperature is 30-60° C. higher than the primary aging temperature.

[0029] In step (2) of the present invention, the drying temperature after secondary aging is 120-180°C, the drying time is 2-10 hours, and filtering and washing can be performed according to conventional known methods before drying. The dry basis content of the dried product I and the dried product II obtained after drying is 30wt%-70wt%.

[0030] In step (3) of the present invention, the mass percentage concentration of the ammonium bicarbonate aqueous solution ranges from 10% to 20%. The sealing heat treatment temperature is 80 to 140°C, preferably 110 to 140°C, and the treatment time is 6 to 12 hours. The drying temperature is 120 to 180°C, and the drying time is 2 to 10 hours.

[0031] In step (4) of the present invention, the mass percentage concentration of the aqueous solution of ammonium bicarbonate is in the range of 20% to 30%. The sealing heat treatment temperature is 80 to 140°C, preferably 80 to 110°C, wherein the heat treatment temperature in step (4) is 30 to 50°C lower than the heat treatment temperature in step (3), and the treatment time is 6 to 12 hours. The drying temperature is 120 to 180°C, and the drying time is 2 to 10 hours.

[0032] The mass concentration of the aqueous ammonium bicarbonate solution in step (4) of the present invention is 8 to 15 percentage points higher than the mass concentration of the aqueous ammonium bicarbonate solution in step (3).

[0033] In step (4) of the present invention, in the unsaturated impregnation, the amount of the first active component metal impregnation solution used accounts for 10% to 40% of the saturated water absorption of the impregnated material.

[0034] In step (4) of the present invention, the first active component metal impregnation liquid is an impregnation liquid containing Mo and a Group VIII metal (preferably Ni), wherein the active metal component molybdenum is derived from one or both of molybdenum oxide and ammonium heptamolybdate, and nickel is derived from one or both of basic nickel carbonate and nickel nitrate, and the contents of MoO3 and Group VIII metal oxide in the first active component metal impregnation liquid are 30.0-80.0 g / 100 ml and 5.0-40.0 g / 100 ml, respectively. The amount of MoO3 introduced into the catalyst by the first active component metal impregnation liquid is 35%-65% of the total MoO3 loading in the catalyst; the amount of Group VIII metal oxide introduced into the catalyst by the first active component metal impregnation liquid is 35%-65% of the total Group VIII metal oxide loading in the catalyst.

[0035] In step (4) of the present invention, at least one auxiliary agent containing fluorine, phosphorus, silicon or boron may also be introduced into the first active component metal impregnation solution, and the amount of the auxiliary agent (calculated as oxide) added is 18% to 28% of the total mass of molybdenum oxide in the first active component metal impregnation solution, preferably 20% to 25%.

[0036] In step (4) of the present invention, preferably, the first active component metal impregnation solution further contains a water-soluble polymer J2. The water-soluble polymer J2 is one or more of polyethylene glycol, polyvinyl alcohol, polyacrylamide and methyl cellulose. The viscosity of the water-soluble polymer J2 is 10 to 1000 mPa·s, and the slurry viscosity (20°C) after adding the water-soluble polymer J2 is 150 to 800 mPa·s.

[0037] In step (4) of the present invention, the impregnation is carried out by spraying, and the spraying time is 15 to 35 minutes.

[0038] In step (4) of the present invention, after the impregnation is completed, the mixture is first dried at 20-40° C. for 2-8 hours, and then dried at 120-200° C. for 2-12 hours.

[0039] In step (5) of the present invention, material A accounts for 15% to 45% of the total mass of material A and material B. In the molding process, conventional molding aids such as one or more of peptizing agents and extrusion aids can be added as needed, wherein the peptizing agent is one or more of nitric acid, sulfuric acid, and oxalic acid, and the extrusion aid is one or more of sesbania powder, cellulose, and resin.

[0040] In step (5) of the present invention, the drying temperature is 20 to 200° C. and the drying time is 2 to 12 hours.

[0041] In step (5) of the present invention, the first calcination temperature is 500-750° C., the calcination time is 2-6 hours, and the calcination atmosphere is an inert atmosphere (such as nitrogen) or water vapor, preferably water vapor.

[0042] In step (6) of the present invention, the second active component metal impregnation liquid contains an impregnation liquid of Mo and a Group VIII metal (preferably Ni), wherein the active metal component molybdenum is derived from one or both of molybdenum oxide and ammonium heptamolybdate, and nickel is derived from one or both of basic nickel carbonate and nickel nitrate. The amount of MoO3 introduced into the catalyst by the second active component metal impregnation liquid is 35% to 65% of the total MoO3 loading in the catalyst; the amount of Group VIII metal oxide introduced into the catalyst by the second active component metal impregnation liquid is 35% to 65% of the total Group VIII metal oxide loading in the catalyst.

[0043] In step (6) of the present invention, preferably, the second active component metal impregnation solution further contains a water-soluble polymer J3. The water-soluble polymer J3 is one or more of polyethylene glycol, polyvinyl alcohol, polyacrylamide and methyl cellulose. The viscosity (20°C) of the water-soluble polymer J3 is 10 to 1000 mPa·s, and the slurry viscosity (20°C) after adding the water-soluble polymer J3 is 150 to 800 mPa·s.

[0044] In step (6) of the present invention, the impregnation is carried out by spraying, and the spraying time is 15 to 35 minutes.

[0045] In step (6) of the present invention, the drying temperature is 120 to 200° C. and the drying time is 2 to 12 hours.

[0046] In step (6) of the present invention, the second calcination temperature is 350-450° C., the calcination time is 2-6 hours, and the calcination atmosphere is an inert atmosphere (such as nitrogen) or water vapor, preferably water vapor.

[0047] Compared with the prior art, the present invention has the following beneficial effects:

[0048] For hydrodemetallization catalysts, good pore structure and reasonable distribution of active metals on the catalyst are of great significance for the catalytic performance. The reduction temperature of tetrahedral Mo species is greater than that of octahedral Mo species, so the presence of tetrahedral Mo has an adverse effect on weakening the interaction between the carrier and the metal, thereby affecting the activity and stability of the catalyst. The inventors have found through extensive research that the carrier is first optimized, the slurry obtained after the neutralization reaction is aged in two stages, and the obtained slurry is treated with and without adding a water-soluble polymer before the secondary aging, and the secondary aging is performed at a higher temperature, so that a porous material with suitable specific surface area and different pore size distribution can be obtained, namely, dried material I and dried material II; then, dried material I is immersed in an aqueous solution of ammonium bicarbonate and then sealed and heat treated to obtain material A, and dried material II is also immersed in an aqueous solution of ammonium bicarbonate and then sealed and heat treated, and at the same time, the first active component metal impregnation solution is sprayed on the dried material II treated with ammonium bicarbonate in an unsaturated impregnation manner to obtain material B. Material A and material B are kneaded and formed, and after drying and first calcination, a carrier is obtained; finally, the second active component metal impregnation solution is loaded on the obtained carrier in a saturated impregnation manner, and then a second calcination is performed to make the ratio of tetrahedral molybdenum and octahedral molybdenum species in the catalyst appropriate. During the preparation of the carrier, the dried material I and the dried material II are respectively subjected to ammonium bicarbonate heat treatment, and a macroporous structure can be formed in the subsequent calcination process, which is beneficial to adjust the pore structure of the carrier on the one hand, and provide a suitable pore structure for the diffusion of macromolecules in the residual oil; on the other hand, it can also provide more possible places for the deposition of metals in the residual oil, thereby improving the metal capacity of the catalyst. Preferably, water-soluble polymers are added to the metal impregnation solutions of the first and second active components, which can promote the dispersion of active metals on the one hand, and appropriately adjust the acidity of the catalyst on the other hand. The method of the present invention significantly improves the activity and stability of the residual oil hydrodemetallization catalyst finally obtained through the comprehensive coordination of various steps. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 This is a Raman spectrum of the catalyst surface obtained in Example 1;

[0050] Figure 2 This is a Raman spectrum of the catalyst surface obtained in Comparative Example 1;

[0051] Figure 3 This is a Raman spectrum of the catalyst surface obtained in Comparative Example 2;

[0052] Figure 4 This is the Raman spectrum of the catalyst surface obtained in Comparative Example 3. DETAILED DESCRIPTION

[0053] In the present invention, the Raman spectroscopic characterization of the catalyst was performed using a DXR Microscope type DXR micro Raman spectrometer from Thermo Scientific. -1 The peak nearby is the peak of tetrahedral molybdenum, at 960 cm -1 The nearby peak is the peak of octahedral molybdenum, and the contents of tetrahedral molybdenum and octahedral molybdenum are calculated based on the area under the same baseline.

[0054] In the present invention, the ASAP-2420 physical adsorption instrument produced by Michael Company is used to characterize the pore structure (SVD) and specific surface area of ​​the catalyst.

[0055] The technical solutions and effects of the present invention are further described below in conjunction with embodiments, but are not limited to the following embodiments.

[0056] Example 1

[0057] 1.5L of aluminum sulfate aqueous solution (the concentration of Al2O3 is 10.0g / 100mL, the initial temperature is 75°C) is introduced from the top into a reactor equipped with 5L of pure water, a stirrer and a heating jacket, and 1L of sodium aluminate aqueous solution (the concentration of Al2O3 is 28.0g / 100mL, the initial temperature is 110°C) is introduced from the bottom of the reactor into the reactor, and the neutralization reaction temperature is controlled at 105°C; aluminum sulfate solution and sodium aluminate solution are added continuously, and the pH value is controlled to 8.5, and the reaction is carried out for 60 minutes; after the parallel flow is completed, an aging is carried out, and the aging temperature is 140°C , aging time is 120 minutes, aging pH value is 9.3; after the first aging, concentrate to the slurry volume to 5L, and evenly divide into two parts, namely slurry I and slurry II, add 25g of polyvinyl alcohol (viscosity is 30mPa·s) to slurry II, the viscosity of the slurry after adding polyvinyl alcohol (20℃) is 260mPa·s, and slurry I is not treated in any way, then both slurry I and slurry II are heated to 170℃, and secondary aging is carried out, the aging time is 120 minutes, and washed and dried to obtain dry matter I and dry matter II with a dry basis of 50wt% respectively;

[0058] Take 100g of dried material I, place it in 300g of ammonium bicarbonate aqueous solution with a mass percentage concentration range of 18%, mix it well, and transfer it into an autoclave for sealed heat treatment at a treatment temperature of 135°C for 6 hours. Then filter the obtained sample and dry it at 175°C for 4 hours to obtain material A. Similarly, take 100g of dried material II, place it in 300g of ammonium bicarbonate aqueous solution with a mass percentage concentration range of 26%, mix it well, and transfer it into an autoclave for sealed heat treatment at a treatment temperature of 85°C for 10 hours. The obtained sample was then filtered and dried at 145°C for 4h. The dried product II after heat treatment was then sprayed with the first active component metal impregnation solution (the content of MoO3 was 66.1g / 100ml, the content of NiO was 15.1g / 100ml, and the amount of P (in terms of oxide) in the auxiliary phosphoric acid was 23.6% of the total mass of molybdenum oxide in the impregnation solution) (the amount of the first active component metal impregnation solution was 22% of the saturated water absorption of the dried product II), and polypropylene was added to the first active component metal impregnation solution. Amide (viscosity of 950mPa·s), the viscosity after addition is 650mPa·s, wherein the amount of MoO3 introduced into the catalyst by the first active component metal impregnation liquid is 40% of the total MoO3 loading in the catalyst; the amount of NiO introduced into the catalyst by the first active component metal impregnation liquid is 40% of the total NiO loading in the catalyst, the spraying time is controlled within 30min, and then at room temperature of 25°C, it is allowed to stand and dry for 2h, and then the obtained sample is dried at 120°C for 6h to obtain material B;

[0059] Material A and material B were kneaded in a mass ratio of 1:4, and 3.0wt% acetic acid and 2.0wt% sesbania powder were added during the molding process. The molded sample was dried at 120°C for 4 hours. The carrier was then calcined at 750°C for 3 hours in a steam atmosphere to obtain a catalyst carrier containing some active metals.

[0060] Weigh 200g of the catalyst carrier containing some active metals, and perform secondary impregnation with the second active component metal impregnation liquid in a saturated impregnation manner, and add polyacrylamide (viscosity of 950mPa·s) to the second active component metal impregnation liquid, and the viscosity after addition is 350mPa·s, wherein the amount of MoO3 introduced into the catalyst by the second active component metal impregnation liquid is 60% of the total MoO3 loading in the catalyst; the amount of NiO introduced into the catalyst by the second active component metal impregnation liquid is 60% of the total NiO loading in the catalyst, the spraying time is controlled within 30min, and then dried at 120℃ for 6h, calcined at 350℃ for 5h, wherein the heating rate of the calcination process is 3℃ / min, and the hydrodemetallization catalyst CAT-1 is obtained. The physicochemical properties of the catalyst are shown in Table 1.

[0061] Example 2

[0062] Compared with Example 1, the difference in this example is that the initial temperature of the sodium aluminate aqueous solution added is 100°C, 50g of polyvinyl alcohol (viscosity of 30mPa·s) is added to the slurry II after the first aging, and the viscosity of the slurry after the addition of polyvinyl alcohol (20°C) is 280mPa·s;

[0063] Take 100g of dried material I, place it in 300g of ammonium bicarbonate aqueous solution with a mass percentage concentration range of 16%, mix it and transfer it into an autoclave for sealed heat treatment, the treatment temperature is 125°C, and the treatment time is 8h. Then filter the obtained sample and dry it at 165°C for 6h to obtain material A. Similarly, take 100g of dried material II, place it in 300g of ammonium bicarbonate aqueous solution with a mass percentage concentration range of 26%, mix it and transfer it into an autoclave for sealed heat treatment, the treatment temperature is 95°C, and the treatment time is 8h. Then filter the obtained sample and dry it at 155°C for 6h, then spray the heat-treated dried material II (same as Example 1) with the first active component metal impregnation solution to obtain material B. Material A and material B are kneaded and formed in a mass ratio of 3:8. In the first calcination process, the temperature was raised to 700°C at a heating rate of 3°C / min for 4h; in the second calcination process, the temperature was raised to 400°C at a heating rate of 3°C / min for 4h to obtain the hydrodemetallization catalyst CAT-2. The physicochemical properties of the catalyst are shown in Table 1.

[0064] Example 3

[0065] Compared with Example 1, the difference of this example is that 100g of dried material I is taken, placed in 300g of ammonium bicarbonate aqueous solution with a mass percentage concentration range of 14%, and then transferred into an autoclave for sealed heat treatment after mixing. The treatment temperature is 135°C and the treatment time is 10h. Then the obtained sample is filtered and dried at 155°C for 8h to obtain material A. Similarly, 100g of dried material II is taken, placed in 300g of ammonium bicarbonate aqueous solution with a mass percentage concentration range of 26%, and then transferred into an autoclave for sealed heat treatment after mixing. The treatment temperature is 105°C and the treatment time is 6h. Then the obtained sample is filtered and dried at 165°C for 8h, and then the dried material II after heat treatment is sprayed with the first active component metal impregnation solution (same as Example 1) to obtain material B. Material A and material B are kneaded and formed in a mass ratio of 1:2. In the first calcination process, the temperature was raised to 650°C at a heating rate of 3°C / min for 5h; in the second calcination process, the temperature was raised to 450°C at a heating rate of 3°C / min for 3h to obtain the hydrodemetallization catalyst CAT-3. The physicochemical properties of the catalyst are shown in Table 1.

[0066] Example 4

[0067] Compared with Example 1, the difference of this example is that 100g of dried material I is taken, placed in 300g of ammonium bicarbonate aqueous solution with a mass percentage concentration range of 12%, and after mixing, it is transferred into an autoclave for sealed heat treatment, the treatment temperature is 140°C, and the treatment time is 12h. Then the obtained sample is filtered and dried at 145°C for 10h to obtain material A. Similarly, 100g of dried material II is taken, placed in 300g of ammonium bicarbonate aqueous solution with a mass percentage concentration range of 26%, and after mixing, it is transferred into an autoclave for sealed heat treatment, the treatment temperature is 110°C, and the treatment time is 6h. Then the obtained sample is filtered, dried at 175°C for 10h, and then the first active component metal impregnation solution is sprayed on the heat-treated dried material II (same as Example 1) to obtain material B. The difference is that the amount of MoO3 introduced into the catalyst by the first active component metal impregnation liquid is 30% of the total MoO3 loading in the catalyst; the amount of NiO introduced into the catalyst by the first active component metal impregnation liquid is 30% of the total NiO loading in the catalyst. In the first calcination process, the temperature was raised to 600°C at a heating rate of 3°C / min for 6h; in the second calcination process, the temperature was raised to 500°C at a heating rate of 3°C / min for 3h to obtain the hydrodemetallization catalyst CAT-4. The physicochemical properties of the catalyst are shown in Table 1.

[0068] Comparative Example 1

[0069] Compared with Example 1, the difference is that the dried product I and the dried product II are not immersed in an aqueous solution of ammonium bicarbonate and then sealed for heat treatment, thereby obtaining a hydrodemetallization catalyst dCAT-1. The physicochemical properties of the catalyst are shown in Table 1.

[0070] Comparative Example 2

[0071] Compared with Example 1, the difference is that the active metal impregnation solution containing the same amount of metal is directly mixed and kneaded with the dried product I and the dried product II (the same processing process as in Example 1) to obtain the hydrodemetallization catalyst dCAT-2. The physicochemical properties of the catalyst are shown in Table 1.

[0072] Comparative Example 3

[0073] Compared with Example 1, the difference is that the concentration of ammonium bicarbonate solution used to treat the dried product I and the dried product II is 12%, the temperature of the sealed heat treatment in the autoclave is 135°C, the treatment time is 6 hours, and the drying temperature after filtration is 175°C, and the drying time is 4 hours. The hydrodemetallization catalyst dCAT-3 is obtained. The physicochemical properties of the catalyst are shown in Table 1.

[0074] Table 1 Physicochemical properties of hydrogenation catalysts

[0075]

[0076] Evaluation test

[0077] The residue oil hydrodemetallization catalysts obtained above, i.e., Examples 1 to 4 and Comparative Examples 1 to 3, were subjected to an activity stability test in a 200 ml fixed bed hydrogenation test apparatus. The reaction conditions were: reaction temperature 390° C., hydrogen partial pressure 15.0 MPa, liquid hourly volume space velocity 1.0 h -1 , the hydrogen-to-oil volume ratio is 800, and during the reaction time of 1200 h, the demetallization rates of various catalysts are shown in Table 3, and the properties of the feedstock oil are shown in Table 2.

[0078] Table 2 Raw oil properties

[0079] Raw oil properties Middle East Residue S, wt% 3.3 Ni, μg / g 30.6 V, μg / g 64.5

[0080] Table 3 Test results of various hydrodemetallization catalysts

[0081]

[0082] It can be seen from Table 1, Table 2 and Table 3 that the hydrodemetallization catalyst prepared by the method of the present invention has a high specific surface area and pore volume, and has high reaction activity and stability, and can well meet the hydrodemetallization process of heavy oil, especially residual oil.

Claims

1. A hydrodemetallization catalyst, comprising a carrier component and a second active component, wherein the second active component comprises molybdenum and a Group VIII metal, the carrier component comprises alumina, carbon and a first active component, wherein the first active component comprises molybdenum and a Group VIII metal; the mass ratio of alumina to carbon in the carrier is 5.5 to 24.5; wherein, In the catalyst, the ratio of tetrahedral molybdenum to octahedral molybdenum, calculated as Mo atoms, is 0.13-0.25; the specific surface area of ​​the catalyst is 165-210 m 2 / g, the pore volume is 0.85~1.10mL / g, and the pore diameter is 17~25nm.

2. The catalyst according to claim 1, characterized in that The mass ratio of alumina to carbon in the carrier is 8.0-13.

5.

3. The catalyst according to claim 1, characterized in that The Group VIII metal in the first active component and the second active component is nickel.

4. The catalyst according to claim 1, characterized in that In the catalyst, based on the mass of the catalyst, the content of MoO3 is 5.0% to 20.0%, and the content of the Group VIII metal oxide is 2.0% to 6.0%.

5. The catalyst according to claim 1, characterized in that The catalyst also includes an auxiliary component, which is selected from at least one of fluorine, phosphorus, silicon or boron. Based on the mass of the catalyst, the content of the auxiliary component in terms of oxide is 1.0% to 4.0%.

6. The catalyst according to claim 5, characterized in that The auxiliary component is phosphorus.

7. The method for preparing the hydrodemetallization catalyst according to any one of claims 1 to 4, comprising the steps of: (1) The acidic aluminum salt solution and the alkaline aluminum salt solution are subjected to a neutralization reaction and aged once to obtain a slurry; (2) the slurry obtained in step (1) is evenly divided into slurry I and slurry II, a water-soluble polymer J1 is added to slurry II, slurry I and slurry II are subjected to secondary aging and drying, respectively, to obtain dried product I and dried product II; the water-soluble polymer J1 is one or more selected from the group consisting of polyethylene glycol, polyvinyl alcohol, polyacrylamide and methyl cellulose; (3) immersing the dried material I obtained in step (2) in an aqueous solution of ammonium bicarbonate, sealing and heat treating, and drying to obtain material A; (4) the dried material II obtained in step (2) is immersed in an aqueous solution of ammonium bicarbonate, sealed and heat treated, dried, and the material is impregnated with a first active component metal impregnation solution in an unsaturated impregnation manner, and dried to obtain material B; (5) kneading material A and material B, forming, drying, and first calcining to obtain a carrier; (6) The support obtained in step (5) is impregnated with the second active component metal impregnation solution in a saturated impregnation manner, dried, and subjected to a second calcination to obtain the catalyst.

8. The preparation method according to claim 7, characterized in that: In step (1), the acidic aluminum salt solution and the alkaline aluminum salt solution are subjected to a parallel neutralization reaction; the concentration of the acidic aluminum salt solution in terms of Al2O3 is 8 g / 100 mL to 28 g / 100 mL; the concentration of the alkaline aluminum salt solution in terms of Al2O3 is 10 g / 100 mL to 50 g / 100 mL.

9. The preparation method according to claim 7, characterized in that: In step (1), the neutralization reaction temperature is 75-120° C., the time is 30-150 minutes, and the pH value of the slurry is controlled to be 6.0-9.8 during the neutralization reaction.

10. The preparation method according to claim 7, characterized in that: In step (1), the primary aging temperature is 90-240°C, the time is 50-240 minutes, and the pH value is 9.0-10.0; and / or, in step (2), the secondary aging temperature is 120-270°C, the time is 40-190 minutes, and the secondary aging temperature is 30-60°C higher than the primary aging temperature.

11. The preparation method according to claim 7, characterized in that: In step (2), the water-soluble polymer J1 added to the slurry II is polyethylene glycol; the viscosity of the water-soluble polymer J1 at 20°C is 10-1000 mPa·s, and the viscosity of the slurry at 20°C after adding the water-soluble polymer J1 is 120-660 mPa·s.

12. The preparation method according to claim 7, characterized in that: In step (2), the drying temperature is 120-180° C., the drying time is 2-10 h, and the dry basis contents of the dried products I and II obtained after drying are both 30 wt %-70 wt %.

13. The preparation method according to claim 7, characterized in that: In step (3), the mass concentration of the aqueous ammonium bicarbonate solution is 10% to 20%; and / or, in step (4), the mass concentration of the aqueous ammonium bicarbonate solution is 20% to 30%, and the mass concentration of the aqueous ammonium bicarbonate solution in step (4) is 8 to 15 percentage points higher than the mass concentration of the aqueous ammonium bicarbonate solution in step (3).

14. The preparation method according to claim 7, characterized in that: In step (3), the sealing heat treatment temperature is 80-140°C, the treatment time is 6-12h, the drying temperature is 120-180°C, and the drying time is 2-10h; and / or, in step (4), the sealing heat treatment temperature is 80-140°C, the treatment time is 6-12h, the drying temperature is 120-180°C, and the drying time is 2-10h; wherein the heat treatment temperature in step (4) is 30-50°C lower than the heat treatment temperature in step (3).

15. The preparation method according to claim 14, characterized in that: In step (3), the sealing heat treatment temperature is 110-140°C, and the treatment time is 6-12 hours; and / or, in step (4), the sealing heat treatment temperature is 80-110°C, and the treatment time is 6-12 hours.

16. The preparation method according to claim 7, characterized in that: In step (4), at least one auxiliary agent containing fluorine, phosphorus, silicon or boron is introduced into the first active component metal impregnation solution, and the amount of the auxiliary agent added in terms of oxide is 18% to 28% of the total mass of molybdenum oxide in the first active component metal impregnation solution.

17. The preparation method according to claim 16, characterized in that: In step (4), the amount of the additive added in terms of oxide is 20% to 25% of the total mass of molybdenum oxide in the first active component metal impregnation solution.

18. The preparation method according to claim 7, characterized in that: In step (4), the amount of the first active component metal impregnation solution used accounts for 10% to 40% of the saturated water absorption of the impregnated material.

19. The preparation method according to claim 7, characterized in that: In step (5), material A accounts for 15% to 45% of the total mass of material A and material B.

20. The preparation method according to claim 7, characterized in that: In step (5), the first calcination temperature is 500-750°C, the calcination time is 2-6 hours, and the calcination atmosphere is an inert atmosphere or water vapor; and / or, in step (6), the second calcination temperature is 350-450°C, the calcination time is 2-6 hours, and the calcination atmosphere is an inert atmosphere or water vapor.

21. The preparation method according to claim 20, characterized in that: In step (5), the calcination atmosphere of the first calcination is water vapor; and / or, in step (6), the calcination atmosphere of the second calcination is water vapor.